M-learning in the field Production Direction through flipped classroom with virtual collaborative environments and its evaluation with rubrics - Sonia Martín-Gómez; Cristina Masa-Lorenzo (Centro de Estudios Financieros, 2017)
This study is part of a teacher change and improvement project whose aim is to modify the traditional teaching system in the field of Production Management (Operations Management), focusing its learning on the acquisition of the competences required by the European Higher Education Area (EHEA), in such a way that the student participates actively and is involved in the solution of the problems of real companies raised in the classroom in a virtual collaborative environment, supported in social networks through the use of different mobile devices (m-learning). Innovative methodologies such as flipped class-room, where we propose that the student begins to play an active role through problem-based collaborative learning (PBCL), whose purpose will be to train students capable of analyzing and facing problems in the same way as they would during their professional activity. However, for this methodological change to be successful, it will have to be accompanied by well-designed rubrics that allow the correct evaluation of group work and participation in the classroom. In this way, the students will know the competences achieved and those that need strengthening.